Development of MEMS Manifold Absolute Pressure Sensor (MAPs) Prototype - Zaliman, Sauli, Assoc. Prof.; Hasnizah, Aris; Johari, Adnan, Assoc. Prof. Dr.; Poopalan, Prabakaran, Assoc. Prof. Dr.; Ramzan, Mat Ayub; Rizalafande, Che Ismail; Sohiful Anuar, Zainol Murad; Azuwir, Md. Nor; Abu Hassan, Abdullah; Mohd. Hatta, Musa; Razaidi, Hussin (Malaysian Invention and Design Society (MINDS), 2010)
Assoc. Prof. Zaliman Sauli and his team from School of Microelectronics Engineering won silver for Development of MEMS Manifold Absolute Pressure Sensor (MAPs) Prototype. ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.